Calcium Enhances Binding of Aβ Monomer to DMPC Lipid Bilayer - Lockhart, Christopher (Biophys J, 2015)
Using isobaric-isothermal replica-exchange molecular dynamics and the all-atom explicit-solvent model, we studied the equilibrium binding of Aβ monomers to a zwitterionic dimyristoylphosphatidylcholine (DMPC) bilayer coincubated with calcium ions. Using our previous replica-exchange molecular dynamics calcium-free simulations as a control, we reached three conclusions. First, calcium ions change the tertiary structure of the bound Aβ monomer by destabilizing several long-range intrapeptide interactions, particularly the salt bridge Asp(23)-Lys(28). Second, calcium strengthens Aβ peptide binding to the DMPC bilayer by enhancing electrostatic interactions between charged amino acids and lipid polar headgroups. As a result, Aβ monomer penetrates deeper into the bilayer, making disorder in proximal lipids and bilayer thinning more pronounced. Third, because calcium ions demonstrate strong affinity to negatively charged amino acids, a considerable influx of calcium into the area proximal to the bound Aβ monomer is observed. Consequently, the localizations of negatively charged amino acids and calcium ions in the Aβ binding footprint overlap. Based on our data, we propose a mechanism by which calcium ions strengthen Aβ-bilayer interactions. This mechanism involves two factors: 1) calcium ions make the DMPC bilayer partially cationic and thus attractive to the anionic Aβ peptide; and 2) destabilization of the Asp(23)-Lys(28) salt bridge makes Lys(28) available for interactions with the bilayer. Finally, we conclude that a single Aβ monomer does not promote permeation of calcium ions through the zwitterionic bilayer.